DIPLOMASI BUDAYA AMERIKA SERIKAT MELALUI HOLLYWOOD DALAM MENGHADAPI PROTEKSIONISME INDUSTRI FILM CHINA PERIODE 2016-2019 - Jatyo Budisaryowo (2023)
This research aims to discuss the United States' effort through Hollywood in facing China's protectionist film industry, as well as to determine whether those efforts affect Hollywood's market share in Chinese market from 2016-2019. This research uses the concepts of: cultural diplomacy, soft power, and protectionism. This is a descriptive qualitative research with primary and secondary data. Data is collected through observation, documentation and literature study. Miles, Huberman, and Saldana's data analysis techniques are used, which include data condensation, data display, and drawing and verifying conclusions. Results show that Hollywood's cultural diplomacy comes in three main types: adaptation and content adjustment, cooperation with Chinese film studios, and the utilization of a globalized American pop culture. Hollywood's market share experienced an increase in the 2016-2017 period, whilst the 2018-2019 period saw a decrease. Regardless, the Chinese market is still the most lucrative source of income for the American film industry.